2016
DOI: 10.1002/cplu.201600229
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylsilanone Generation from Pyrolysis of Polysiloxanes Filled with Nanosized Silica and Ceria/Silica

Abstract: Temperature‐programmed desorption mass spectrometry (TPD MS) was used to study the pyrolysis of PDMS and its composites with nanosized silica and ceria/silica. The results suggest that the elusive organosilicon compound, dimethylsilanone, is generated from PDMS over a broad temperature range (in some cases starting at 70 °C). The presence of nano‐oxides catalyzes this process. Ions characteristic of the fragmentation of dimethylsilanone under electron ionization are assigned with the aid of DFT structure calcu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 68 publications
(225 reference statements)
0
16
0
Order By: Relevance
“…Among the approaches, along with those in principle consisting of chemical modification, a path that offers many design opportunities is the incorporation of suitable active fillers to induce or enhance certain properties. It is known that the incorporation of a small amount of REO into polymers induces significant improvements in their properties, such as thermal stability, conductivity, hydrophobicity, surface or texture properties, etc [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the approaches, along with those in principle consisting of chemical modification, a path that offers many design opportunities is the incorporation of suitable active fillers to induce or enhance certain properties. It is known that the incorporation of a small amount of REO into polymers induces significant improvements in their properties, such as thermal stability, conductivity, hydrophobicity, surface or texture properties, etc [9].…”
Section: Introductionmentioning
confidence: 99%
“…CeO 2 proved to be an efficient reinforcing agent for natural rubber [17]. As additives to silicones, generally, in studies reported in literature [9,18], REO have been used together with silica (Ceria/Silica [9] or Ceria-Zirconia-Silica@PDMS [18]). There is a report in 1974 [19] about the thermostabilizing effect of rare-earth metal oxides on methylvinylsilicone rubbers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the silicone industry chain, monomers play a vital role, which preparation level marks the development level of the silicone industry . The amount of methylchlorosilanes accounts for more than 90% of the total monomers' yield, in which dimethyldichlorosilane((CH 3 ) 2 SiCl 2 , abbreviated as M2) is the most used and most important one . In order to promote the development of the silicone industry, it is important to disproportionate waste silanes into dimethyldichlorosilane.…”
Section: Introductionmentioning
confidence: 99%
“…Their barriers to dissociation have been reported (Davidson and Thompson, 1971) and are too large for decomposition to occur at the inlet temperatures used in this work. However, Kulyk et al (2016) …”
mentioning
confidence: 99%